Outer packaging bag for small-volume liquid drug, and method for manufacturing the outer packaging bag for small-volume liquid drug

The outer bag for small-volume liquid medicine bags uses a polyethylene terephthalate layer with terephthalic and isophthalic acid, combined with a barrier and sealant layer, to maintain barrier function and visibility, addressing deformation-induced issues and drug concentration fluctuations.

JP7604956B2Active Publication Date: 2024-12-24TOPPAN HOLDINGS INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021037148
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-09
Publication Date
2024-12-24
Estimated Expiration
2041-03-09

AI Technical Summary

Technical Problem

Existing outer bags for small-volume liquid medicine bags face challenges in maintaining barrier function against oxygen and moisture permeation, especially under conditions of deformation such as folding and twisting, which can lead to fluctuations in drug concentration and reduced visibility.

Method used

The outer bag design incorporates a polyethylene terephthalate layer containing terephthalic and isophthalic acid in dicarboxylic acid units, combined with a barrier layer and a thermoplastic sealant layer, which can include an inorganic oxide layer, and optionally a polypropylene protective layer, to enhance durability and visibility while maintaining barrier function.

Benefits of technology

The design effectively suppresses deterioration of the barrier function during deformation, maintains drug concentration, and ensures transparency, while also reducing the occurrence of pinholes and improving the durability of the printed layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604956000003
    Figure 0007604956000003
  • Figure 0007604956000004
    Figure 0007604956000004
  • Figure 0007604956000005
    Figure 0007604956000005
Patent Text Reader

Abstract

To provide an outer packaging bag for small capacity solution and manufacturing method, capable of suppressing a barrier function from degrading.SOLUTION: An outer packaging bag for small capacity solution, used for packaging a small capacity solution bag, includes: a barrier layer 23; a sealant layer 21 with thermoplasticity; and a polyethylene terephthalate layer 22 positioned between the barrier layer 23 and the sealant layer 21. The polyethylene terephthalate layer 22 includes polyethylene terephthalate containing terephthalic acid and isophthalic acid by a dicarboxylic acid unit in a repeating unit.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an outer pouch for a small-volume liquid agent for packaging a small-volume liquid agent bag, and a method for manufacturing the outer pouch for a small-volume liquid agent. [Background technology]

[0002] Outer bags for packaging liquid medicine bags are required to have a barrier function that suppresses the transmission of oxygen and moisture. Outer bags that utilize the barrier function of an aluminum layer have excellent barrier function, but they lose the visibility of the liquid medicine passing through the outer bag. Outer bags for infusion preparations and other products that require the visibility of the liquid medicine are used as a barrier layer in place of an aluminum layer, using a transparent vapor deposition film in which an aluminum oxide layer or a silicon oxide layer is laminated onto a nylon layer or a polyester layer (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-140327 A Summary of the Invention [Problem to be solved by the invention]

[0004] From the viewpoint of the barrier function required for the outer bag, the outer bag of the liquid agent bag is classified into a small-capacity outer bag for packaging a small-capacity liquid agent bag of 250 ml or less and a large-capacity outer bag for packaging a large-capacity liquid agent bag of 500 ml or more. Whether the outer bag is a small-capacity outer bag or a large-capacity outer bag, the evaporation of water from the liquid agent bag causes the concentration of the liquid agent to deviate from the required value. On the other hand, even if the amount of components evaporated from the outer bag is about the same between the large-capacity outer bag and the small-capacity outer bag, the composition variation of the liquid agent in the liquid agent bag is relatively large in the small-capacity liquid agent bag. In particular, during the distribution process of the outer bag packaging the liquid agent bag, the liquid agent is subjected to shaking and vibration, and deformations such as folding and twisting that reduce the barrier function are repeated in the outer bag. In view of this situation, the outer bag packaging the small-capacity liquid agent bag is required to suppress the reduction in the barrier function. [Means for solving the problem]

[0005] The outer bag for small-volume liquid agent to solve the above-mentioned problems is an outer bag for small-volume liquid agent for packaging a small-volume liquid agent bag, and includes a barrier layer, a sealant layer having thermoplastic properties, and a polyethylene terephthalate layer located between the barrier layer and the sealant layer, and the polyethylene terephthalate layer contains polyethylene terephthalate containing terephthalic acid and isophthalic acid in dicarboxylic acid units in the repeating units.

[0006] A manufacturing method for an outer bag for a small-volume liquid agent to solve the above-mentioned problems is a manufacturing method for an outer bag for a small-volume liquid agent for packaging a small-volume liquid agent bag, and includes laminating a barrier layer on a polyethylene terephthalate layer, and laminating a sealant layer having thermoplastic properties on the polyethylene terephthalate layer so that the polyethylene terephthalate layer is sandwiched between the barrier layer and the sealant layer, wherein the polyethylene terephthalate layer contains polyethylene terephthalate containing terephthalic acid and isophthalic acid in dicarboxylic acid units in the repeating units.

[0007] According to each of the above configurations, since the dicarboxylic acid units in the repeating units contain polyethylene terephthalate containing terephthalic acid and isophthalic acid, it is possible to suppress the deterioration of the barrier function of the outer bags for small-volume liquid agents due to deformation such as folding or twisting.

[0008] In the above-mentioned outer bag for small-volume liquid agent, the barrier layer may be an inorganic oxide layer, and the outer bag for small-volume liquid agent may be transparent. With this configuration, it is possible to improve the visibility of the liquid agent bag through the outer bag for small-volume liquid agent. In addition, since the configuration does not employ a metal barrier layer having a high barrier function, it is more advantageous to suppress the deterioration of the barrier function of the polyethylene terephthalate layer.

[0009] The small-volume liquid agent outer bag may further include a polypropylene layer, and the barrier layer may be located between the polypropylene layer and the polyethylene terephthalate layer. According to the above-mentioned configuration, since the polypropylene layer protects the barrier layer, it is more effective in suppressing the deterioration of the barrier function. In addition, when the polypropylene layer is positioned as the outermost layer, it is also possible to suppress the occurrence of pinholes in the small-volume liquid agent outer bag.

[0010] The small-volume liquid agent outer bag may further include a printed layer, and the printed layer may be located between the polypropylene layer and the barrier layer. According to the above-mentioned configuration, since the polypropylene layer protects the printed layer, it is possible to suppress a decrease in durability of the printed layer caused by deformation such as folding, twisting, etc. In addition, the barrier layer located between the printed layer and the liquid agent bag also has a barrier function against the components of the printed layer.

[0011] In the above-mentioned outer bag for small-volume liquid agent, the proportion of isophthalic acid in the total dicarboxylic acid units of the polyethylene terephthalate layer may be 0.5 mol% or more and 5 mol% or less. According to this configuration, since the proportion of isophthalic acid is 0.5 mol% or more and 5 mol% or less, it is possible to enhance the effectiveness of obtaining the above-mentioned effects.

[0012] In the above-mentioned exterior bag for a small-volume liquid agent, the small volume may be 100 ml or less. With this configuration, the surface area of ​​the liquid agent per unit volume that comes into contact with the exterior bag is particularly large, which results in a more remarkable effect in preventing the deterioration of the barrier function. Effect of the Invention

[0013] According to the present invention, it is possible to provide an outer pouch for a small-volume liquid agent, which is capable of suppressing a decrease in the barrier function, and a method for manufacturing such an outer pouch. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a diagram showing a front structure of an embodiment of an outer bag for a small-capacity liquid agent. [Diagram 2] FIG. 2 is a cross-sectional view showing a cross-sectional structure of one embodiment of an outer bag for a small-capacity liquid agent. [Diagram 3] Graph showing an example of a stress-strain curve. [Figure 4] Graph showing storage elasticity curves of each test example. [Diagram 5] Graph showing loss elasticity curves of each test example. [Figure 6] Graph showing loss tangent curves for each test example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] An embodiment of an outer pouch for a small-volume liquid agent and a method for manufacturing the outer pouch for a small-volume liquid agent will be described. [Configuration of the exterior bag 10 for small-volume liquid agent] As shown in Fig. 1, the small-volume liquid agent outer bag 10 packages a small-volume liquid agent bag and seals the liquid agent bag. The periphery of the small-volume liquid agent outer bag 10 has a sealing portion 11. The small-volume liquid agent outer bag 10 shown in Fig. 1 is a four-sided sealed type outer bag in which the entire periphery of the small-volume liquid agent outer bag 10 is the sealing portion 11. The four-sided sealed type small-volume liquid agent outer bag 10 is manufactured by heat-sealing the edges located on each of the four sides of two rectangular laminates 20.

[0016] The small-volume liquid drug outer bag 10 may be a three-sided sealed outer bag. The three-sided sealed outer bag 10 for small-volume liquid drug is manufactured by folding one rectangular laminate 20 in half and heat-sealing the three edges of the folded laminate 20. Alternatively, the small-volume liquid drug outer bag 10 may be any one selected from the group consisting of a two-sided sealed outer bag, a side sealed outer bag, a self-supporting outer bag, a pillow sealed outer bag, a pleated sealed outer bag, a flat-bottom sealed outer bag, and a square-bottom sealed outer bag. The small-volume liquid drug outer bag 10 may be a one-piece type outer bag or a two-piece type outer bag.

[0017] The liquid bag packaged by the small-volume liquid outer bag 10 contains an infusion preparation and a highly pharmacologically active agent. The infusion preparation is an injection preparation of 50 ml or more intended to enhance the therapeutic effect by administration to the body, and a dissolving agent or diluent of 50 ml or more intended to administer a drug. The infusion preparation includes an electrolyte infusion preparation, a water infusion preparation, a nutrition infusion preparation, a plasma expander, and an osmotic diuretic. The electrolyte infusion includes an isotonic infusion, a hypotonic infusion, and a hypertonic infusion. The hypotonic infusion includes an initiation solution, an extracellular fluid replacement solution, a dehydration replacement solution, a maintenance solution, and a postoperative recovery solution. The nutrition infusion preparation includes a carbohydrate infusion, a fat emulsion, and an amino acid solution. The plasma expander includes a colloid infusion, and a plasma agent. The highly pharmacologically active agent includes a drug solution adjusted to an administration concentration such as an antibiotic, an anticancer drug, or a steroid preparation.

[0018] The capacity of the liquid agent bag packaged in the small-volume liquid agent outer bag 10 is 50 ml or more and 250 ml or less. From the viewpoint of enhancing the suppression of the deterioration of the barrier function, the capacity of the liquid agent bag packaged in the small-volume liquid agent outer bag 10 is preferably 50 ml or more and 100 ml or less.

[0019] [Configuration of sealant layer 21] 2, the laminate 20 includes a sealant layer 21, a polyethylene terephthalate layer 22 (hereinafter also referred to as a PET layer 22), and a barrier layer 23. The PET layer 22 is located between the sealant layer 21 and the barrier layer 23.

[0020] The sealant layer 21 has thermoplasticity that allows heat fusion between one part of the sealant layer 21 and another part. The sealing part 11 of the outer packaging bag 10 for a small-volume liquid agent is formed by heat fusion of the sealant layer 21. The sealant layer 21 may be composed of one layer or may be composed of multiple layers. When the sealant layer 21 is composed of multiple layers, the layers constituting the sealant layer 21 may be composed of the same material or may be composed of different materials.

[0021] The constituent material of the sealant layer 21 may be a linear polyolefin or a cyclic polyolefin. Examples of linear polyolefins include ethylene-based resins, propylene-based resins, ethylene-propylene copolymers, and esters of ethylene-α,β-unsaturated carboxylic acid copolymers. Examples of cyclic polyolefins include ring-opening metathesis polymers (COP) of cyclic olefins, and cyclic olefin copolymers (COC).

[0022] When it is required to further improve the sealing property of the outer bag 10 for a small-volume liquid agent, the thickness of the sealant layer 21 is preferably 20 μm or more, and more preferably 30 μm or more. When it is required to improve the processability of the sealing portion 11, the thickness of the sealant layer 21 is preferably 100 μm or less, and more preferably 70 μm or less.

[0023] When it is required to suppress the elution of the liquid agent from the small-volume liquid agent outer bag 10, the constituent material of the sealant layer 21 is preferably an ethylene-based resin, and more preferably low-density polyethylene.

[0024] When the small-volume liquid drug exterior bag 10 is required to have light-shielding properties, the sealant layer 21 preferably has a three-layer structure including two layers containing a white pigment and one layer containing a black pigment, with the layer containing the black pigment being located between the two white layers. Examples of white pigments include titanium oxide, barium oxide, aluminum hydroxide, and zinc oxide. Examples of black pigments include carbon black, graphite, and aniline black.

[0025] [Configuration of Barrier Layer 23] The barrier layer 23 suppresses the transmission of oxygen and water vapor. The barrier layer 23 may be composed of one layer or multiple layers. When the barrier layer 23 is composed of multiple layers, the layers constituting the barrier layer 23 may be composed of the same material or different materials.

[0026] The barrier layer 23 is at least one selected from the group consisting of an inorganic oxide layer, a metal layer, and a resin film. The constituent material of the inorganic oxide layer is at least one selected from the group consisting of silicon oxide, magnesium oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, potassium oxide, tin oxide, boron oxide, yttrium oxide, etc. The constituent material of the metal layer is at least one selected from the group consisting of aluminum, titanium, zirconium, yttrium, tin, chromium, and nickel. One example of the constituent material of the resin film is a saponified ethylene-vinyl acetate copolymer.

[0027] When uniformity in the thickness of the barrier layer 23 is required, the thickness of the barrier layer 23 is preferably 5 nm or more, and more preferably 10 nm or more. When further suppression of crack generation due to bending is required for the barrier layer 23, the thickness of the barrier layer 23 is preferably 300 nm or less, and more preferably 150 nm or less.

[0028] When transparency is required for the outer package 10 for a small-volume liquid agent, the material constituting the barrier layer 23 is preferably an inorganic oxide. When a reduction in the barrier function against water vapor is further required in addition to transparency, the material constituting the barrier layer 23 is more preferably silicon oxide.

[0029] [Configuration of PET layer 22] The repeating units of polyethylene terephthalate (hereinafter also referred to as PET) constituting the PET layer 22 include a diol unit and a dicarboxylic acid unit. The PET constituting the PET layer 22 includes PET containing terephthalic acid and isophthalic acid in the dicarboxylic acid unit.

[0030] When it is required to soften the outer bag 10 for a small-volume liquid agent and further suppress the decrease in the barrier function, the ratio of isophthalic acid to all dicarboxylic acid units in the PET layer 22 is preferably 0.5 mol % or more. When it is required to stabilize the shape of the outer bag 10 for a small-volume liquid agent, the ratio of isophthalic acid to all dicarboxylic acid units is preferably 5 mol % or less.

[0031] When the small-volume liquid drug outer bag 10 is required to reduce the environmental load, the PET constituting the PET layer 22 may include recycled PET, which is regenerated PET. PET products to be recycled include used PET bottles. The recycled PET constituting the PET layer 22 is at least one of PET regenerated by mechanical recycling and PET regenerated by chemical recycling.

[0032] In mechanical recycling, PET products are crushed and washed to remove surface dirt and foreign matter, and then the resin is exposed to high temperatures to remove contaminants that remain inside the resin.In chemical recycling, PET products are crushed and washed to remove surface dirt and foreign matter, and then the resin is depolymerized to return it to its intermediate raw material, which is then refined and repolymerized to produce PET.

[0033] When further reduction in manufacturing cost and environmental load is required for the outer bag 10 for a small-volume liquid agent, the recycled PET constituting the PET layer 22 is preferably PET regenerated by mechanical recycling. Compared with chemical recycling, mechanical recycling does not require large-scale facilities for chemical reactions, so the cost and environmental load required for manufacturing the recycled PET are small.

[0034] The constituent material of the PET layer 22 may include virgin PET, which is a PET newly synthesized from raw materials such as petroleum, in addition to recycled PET, or may include polyester other than recycled PET. The mass ratio of the recycled PET constituting the PET layer 22 is preferably 60% or more and 100% or less of the total mass of the PET layer 22.

[0035] The diol unit of virgin PET is ethylene glycol, and the dicarboxylic acid unit of virgin PET is terephthalic acid. In contrast, the dicarboxylic acid that is the raw material of PET that constitutes PET bottles contains isophthalic acid in addition to terephthalic acid to improve the processability of the resin when molding the bottle.

[0036] Isophthalic acid shortens the main chain of PET compared to PET made only of terephthalic acid, suppresses crystallization of PET, and improves the processability of PET. The diol unit of PET that constitutes PET bottles may contain diethylene glycol in addition to ethylene glycol, or it may be only ethylene glycol.

[0037] The average molecular weight of the PET constituting the PET layer 22 is not particularly limited, but is preferably, for example, 1,000 to 1,000,000. The material constituting the PET layer 22 may contain resins other than PET and various additives. The additives include, for example, plasticizers, color inhibitors, antistatic agents, weather resistance agents, ultraviolet absorbers, deodorizers, and antioxidants.

[0038] The PET layer 22 may be composed of one layer or may be a laminate composed of multiple layers. When the PET layer 22 is a laminate, at least one layer of the laminate contains PET containing terephthalic acid and isophthalic acid in the dicarboxylic acid unit.

[0039] The constituent material of the PET layer 22 may include polyester other than recycled PET and virgin PET. The polyester other than recycled PET and virgin PET has, for example, a chain aliphatic carboxylic acid or a cyclic aliphatic carboxylic acid as a carboxylic acid unit.

[0040] When durability and impact resistance are required for the small-volume liquid agent outer bag 10, the thickness of the PET layer 22 is preferably 3 μm or more, and more preferably 10 μm or more. When processability is required for the small-volume liquid agent outer bag 10, the thickness of the PET layer 22 is preferably 50 μm or less, and more preferably 30 μm or less.

[0041] The PET layer 22 can be formed by a known film forming method such as extrusion molding. The cooling in the extrusion molding can be performed by a known method such as cooling roll, air cooling, or water cooling. The PET layer 22 may be a stretched film or a non-stretched film. The PET layer 22 can be stretched by a known method such as uniaxial stretching or biaxial stretching.

[0042] [Surface protection and display] The small-volume liquid agent outer bag 10 may further include a protective layer for suppressing the occurrence of pinholes on the outer side of the small-volume liquid agent outer bag 10 relative to the barrier layer 23. The protective layer is made of biaxially oriented polypropylene. The biaxially oriented polypropylene layer satisfies the heat resistance in the sealing process using the sealant layer 21. The biaxially oriented polypropylene layer is also preferable from the viewpoint of increasing the rigidity and puncture resistance of the laminate 20.

[0043] The outer bag 10 for small-volume liquid agent may include a printed layer between the barrier layer 23 and the protective layer. The printed layer displays characters, figures, symbols, patterns, etc. formed by printing. The outer bag 10 for small-volume liquid agent may include a printed layer between the PET layer 22 and the sealant layer 21. The outer bag 10 for small-volume liquid agent may further include an anchor coat layer serving as a base for the printed layer between the printed layer and the barrier layer 23 or between the printed layer and the PET layer 22. The constituent material of the anchor coat layer is an anchor coat agent such as an isocyanate compound, polyethyleneimine, or an organic titanate compound.

[0044] [Method of manufacturing the exterior bag 10 for small-volume liquid agent] The manufacturing method of the small-volume outer bag 10 for a small-volume liquid agent includes forming a laminate 20, and manufacturing the small-volume outer bag 10 from the laminate 20. Forming the laminate 20 includes laminating a barrier layer 23 on a PET layer 22, and laminating a sealant layer 21 on the PET layer 22. Manufacturing the small-volume outer bag 10 includes heat-sealing the sealant layers 21 together.

[0045] The barrier layer 23 can be laminated on the PET layer 22 by a known film-forming method such as vapor deposition, sputtering, ion plating, or plasma CVD, or by laminating the PET layer 22 with a metal foil or resin film.

[0046] The method for laminating the sealant layer 21 on the PET layer 22 may be a dry lamination method, an extrusion lamination method, or a sandwich lamination method using the extrusion lamination method. A known lamination adhesive may be used as the adhesive used in the dry lamination method. The lamination adhesive may be any one selected from the group consisting of polyurethane-based, polyacrylic-based, polyester-based, epoxy-based, polyvinyl acetate-based, and cellulose-based adhesives.

[0047] In addition, when the outer bag 10 for small-volume liquid agent has a protective layer, a printing layer, and an anchor coat layer on the outside of the barrier layer 23, each layer may be laminated on the barrier layer 23 before the sealant layer 21 is laminated on the PET layer 22, or each layer may be laminated on the barrier layer 23 after the sealant layer 21 is laminated on the PET layer 22.

[0048] When the outer bag 10 for small-volume liquid agent has a printing layer and an anchor coat layer on the inside of the barrier layer 23, each layer may be laminated on the PET layer 22 before the barrier layer 23 is laminated on the PET layer 22, or each layer may be laminated on the PET layer 22 after the barrier layer 23 is laminated on the PET layer 22.

[0049] The method for producing the outer bag 10 for small-volume liquid agent is to heat-seal the sealant layers 21 together to form the sealed portion 11. Examples of the heat seal type for forming the sealed portion 11 include a side seal type, a two-sided seal type, a three-sided seal type, a four-sided seal type, an envelope-pasted seal type, a pillow seal type, a pleated seal type, a flat-bottom seal type, and a square-bottom seal type. Examples of the method for forming the sealed portion 11 include a bar seal, a rotary roll seal, a belt seal, an impulse seal, a high-frequency seal, and an ultrasonic seal.

[0050] In one example of forming the sealing portion 11, two rectangular laminates 20 are used. The two laminates 20 are stacked such that the sealant layers 21 located on the four sides of the two laminates 20 are in contact with each other. The sealant layers 21 located on the four sides are heat-sealed to form a four-side-sealed outer bag 10 for a small-volume liquid agent.

[0051] Another example of forming the sealing portion 11 uses one rectangular laminate 20. One laminate 20 is folded in half so that the sealant layers 21 of the laminate 20 are in contact with each other. Next, the sealant layers 21 on three sides of the folded laminate 20 are heat-sealed to form a three-side sealed outer bag 10 for a small-volume liquid agent.

[0052] Another example of forming the sealing portion 11 uses one laminate 20 having a rectangular shape. The laminate 20 is bent into a cylindrical shape so that the sealant layer 21 of the one laminate 20 is on the inside. The sealant layers 21 located at the connection parts of the cylindrical surface are heat-sealed to each other to form a back-attaching portion, which is an example of the sealing portion 11. In addition, the sealant layers 21 located at the upper and lower openings of the cylindrical surface are heat-sealed to each other to manufacture the remaining part of the sealing portion 11.

[0053] [Stress characteristics of PET layer 22] When it is required to further suppress the deterioration of the barrier function, it is preferable that the PET layer 22 satisfies the following conditions 1 to 3 in the stress-strain curve of the PET layer 22. The stress-strain curve is measured based on a tensile test in accordance with JIS K7161-1:2014.

[0054] (Condition 1) The yield stress in the flow direction is 109 MPa or more and 117 MPa or less. (Condition 2) After yielding, and in the range where the strain is 0.2 or more and 0.4 or less, the slope of the stress-strain curve is in the range of 75 or more and 111 or less. (Condition 3) The breaking strength in the machine direction is 153 MPa or more and 183 MPa or less.

[0055] Fig. 3 shows an example of a stress-strain curve obtained by a tensile test on a test piece formed only from the PET layer 22. In the stress-strain curve shown in Fig. 3, the stress at the yield point A indicated by the arrow is the yield stress. Note that in the stress-strain curve, the breaking point B indicated by the arrow is the point at which the test piece breaks, and the stress at point B is the breaking strength.

[0056] 3, the range from the origin to the yield point A, i.e., the range in which stress is proportional to strain, is the range in which the PET layer 22 undergoes elastic deformation. In the range in which elastic deformation occurs, the greater the slope of the stress-strain curve before bending, the harder the PET layer 22 tends to be, and the smaller the slope of the stress-strain curve, the softer the PET layer 22 tends to be. When a pressure exceeding the yield stress is applied to the PET layer 22, the PET layer 22 undergoes plastic deformation.

[0057] The steeper the slope of the stress-strain curve after the yield point A, the harder the PET layer 22 is, and the smaller the difference between the strain at the yield point A and the strain at the break point B tends to be. On the other hand, the steeper the slope of the stress-strain curve after the yield point A, the softer the PET layer 22 is, and the larger the difference between the strain at the yield point A and the strain at the break point B tends to be. The PET layer 22 often has a break point B at a point where the strain exceeds 0.4 in the stress-strain curve, and it is possible to grasp the tendency in the rigidity of the PET layer 22 from the slope at a strain of 0.4 or less.

[0058] The PET layer 22 tends to be harder as the breaking strength at the breaking point B increases, and tends to be tougher as the breaking strength decreases. If the breaking strength is too high, the stress value when the PET layer 22 breaks tends to be large, but the strain that the PET layer 22 can withstand tends to be small. On the other hand, if the breaking strength is too low, the strain that the PET layer 22 can withstand tends to be large, but the stress value when the PET layer 22 breaks tends to be small.

[0059] The area enclosed by the stress-strain curve indicates the ability of the PET layer 22 to absorb impact energy. The smaller the area enclosed by the stress-strain curve, the more brittle, i.e., the less tough, the PET layer 22 tends to be. Conversely, the larger the area enclosed by the stress-strain curve, the less brittle, i.e., the more tough, the PET layer 22 tends to be.

[0060] During distribution of the small-volume liquid agent outer pouch 10 in which the liquid agent bag is packaged, shaking, vibration, and the like act on the liquid agent, and deformations such as folding and twisting that deteriorate the barrier function are repeatedly caused in the small-volume liquid agent outer pouch 10. The barrier layer 23, which is harder than the PET layer 22, is likely to deteriorate in barrier function when subjected to an external force that deforms the small-volume liquid agent outer pouch 10. The PET layer 22 that satisfies conditions 1 to 3 is soft and tough, and therefore consumes the external force that may act on the barrier layer 23 inside the PET layer 22, further suppressing deterioration of the barrier function in the small-volume liquid agent outer pouch 10.

[0061] The yield stress, the slope after yield, and the breaking strength of the PET layer 22 can be adjusted by the temperature at which the PET layer 22 is extruded, the temperature at which the precursor of the extruded PET layer 22 is cooled, the rate at which the precursor is cooled, and the stretching ratio of the PET layer 22. The yield stress, the slope after yield, and the breaking strength of the PET layer 22 can be adjusted by the ratio of isophthalic acid to all dicarboxylic acid units contained in the PET layer 22.

[0062] For example, when it is required to increase the yield stress, the slope after yield, and the breaking strength, these can be adjusted by increasing the temperature during extrusion molding of the PET layer 22, or by decreasing the temperature at which the extruded precursor of the PET layer 22 is cooled. When it is required to decrease the yield stress, the slope after yield, and the breaking strength, these can be adjusted by increasing the cooling rate of the precursor, increasing the stretching ratio of the PET layer 22, or increasing the ratio of isophthalic acid to all dicarboxylic acid units contained in the PET layer 22.

[0063] [Viscoelastic properties of PET layer 22] When it is further required to suppress the degradation of the barrier function, it is preferable that the PET layer 22 satisfies the following condition 4 in a storage elasticity curve showing the relationship between the storage elasticity G1 and the temperature. Also, it is preferable that the PET layer 22 satisfies the following condition 5 in a loss elasticity curve showing the relationship between the loss elasticity G2 and the temperature. Also, it is preferable that the PET layer 22 satisfies the following condition 6 in a loss tangent curve of the PET layer 22 showing the relationship between the loss tangent tanδ and the temperature.

[0064] (Condition 4) The transition temperature T1 from a glassy state to a rubbery state is 80° C. or more and 88° C. or less, and the storage modulus G1 at the transition temperature is 3.8 GPa or more and 4.1 GPa or less. (Condition 5) The temperature T2 at the peak position is 95° C. or more and 102° C. or less, and the loss modulus G2 at the peak position is 0.30 GPa or more and 0.37 GPa or less. (Condition 6) The loss tangent tan δ at the temperature T3 at the peak position is 0.160 or more and 0.190 or less.

[0065] The storage modulus G1 of the PET layer 22 indicates the component of the energy generated in the PET layer 22 by an external force that is stored inside the PET layer 22. The loss modulus G2 of the PET layer 22 indicates the component of the energy generated in the PET layer 22 by an external force that is diffused to the outside as heat. The magnitude of the storage modulus G1 indicates the degree of elasticity, and the magnitude of the loss modulus G2 indicates the degree of viscosity. The loss tangent tanδ is the ratio of the loss modulus G2 to the storage modulus G1 (=G2 / G1), and indicates the balance between elasticity and viscosity in the PET layer 22.

[0066] The weaker the elasticity of the PET layer 22, the lower the responsiveness of the PET layer 22 to the change in shape in response to the application and release of an external force. That is, the movement of the barrier layer 23 following the PET layer 22 also becomes smaller, and the deterioration of the barrier function of the small-volume liquid agent outer package 10 is suppressed. The environmental temperature in which the small-volume liquid agent outer package 10 is used is lower than the transition temperature T1 from the glass state to the rubber state, and the PET layer 22 is used in a glass state with low fluidity. Since the change in the storage elastic modulus G1 when the PET layer 22 is in the glass state is small, the elasticity of the PET layer 22 can be appropriately reflected during use by evaluating the storage elastic modulus G1 at the transition temperature T1.

[0067] The stronger the viscosity of the PET layer 22, the slower the progress of deformation due to application of an external force, and the less likely the deformation is to return to the original state even when the external force is released. That is, even when the application and release of an external force to the PET layer 22 are repeated in a short period of time, the movement of the barrier layer 23 is suppressed, and the deterioration of the barrier function of the small-volume liquid agent outer bag 10 is suppressed. The temperature T2 at the peak position in the loss elasticity curve is a temperature that significantly indicates the viscosity of the PET layer 22. The lower the temperature T2 at the peak position in the loss elasticity curve, the more likely it is that flexibility due to the viscosity will be expressed. However, if the viscosity of the PET layer 22 is excessively large, the processability of the small-volume liquid agent outer bag 10 will decrease, and the strength of the small-volume liquid agent outer bag 10 itself will also decrease.

[0068] The PET layer 22 satisfying the upper limit of the storage modulus G1 in Condition 4 suppresses excessive contribution of elasticity and further suppresses deterioration of the barrier function of the small-volume liquid agent outer bag 10. The PET layer 22 satisfying the lower limit of the storage modulus G1 in Condition 4 suppresses deterioration of suitability as an outer bag.

[0069] The PET layer 22 satisfying the lower limit of the loss modulus G2 in Condition 5 exhibits good flexibility due to viscosity and further suppresses the deterioration of the barrier function in the small-volume liquid agent outer bag 10. The PET layer 22 satisfying the upper limit of the loss modulus G2 in Condition 5 suppresses the deterioration of suitability as an outer bag.

[0070] The PET layer 22 that satisfies the lower limit of the loss tangent tan δ in Condition 6 enhances the viscous properties relative to the elastic properties so as to enhance the vibration absorption in the PET layer 22, thereby further suppressing the deterioration of the barrier function in the small-volume liquid agent outer bag 10. The PET layer 22 that satisfies the upper limit of the loss tangent tan δ in Condition 6 suppresses the deterioration of its suitability as an outer bag.

[0071] The transition temperature T1 from the glassy state to the rubbery state, the temperature T2 at the peak position of the loss elasticity curve, the storage modulus G1, the loss modulus G2 at the peak position of the loss elasticity curve, and the loss tangent tan δ at the peak position of the loss tangent curve can be adjusted by, for example, the proportion of isophthalic acid in the total dicarboxylic acid units of the PET layer 22.

[0072] For example, when it is required to increase the viscosity of the PET layer 22, it can be adjusted by increasing the ratio of isophthalic acid to the total dicarboxylic units of the PET layer 22. When it is required to decrease the storage modulus G1 and increase the loss tangent tanδ, it can be adjusted by lowering the cooling temperature during the manufacture of the PET layer 22. When it is required to increase the loss tangent tanδ and increase the loss modulus G2, it can be adjusted by increasing the cooling rate during the manufacture of the PET layer 22, causing moderate crystal growth, and leaving an amorphous portion. When it is required to decrease the transition temperature T1 from the glass state to the rubber state and decrease the storage modulus G1, it can be adjusted by decreasing the stretch ratio during the manufacture of the PET layer 22 and suppressing molecular orientation.

[0073] [Test example] [Test Example 1] Three resin layers were laminated by coextrusion to form a PET layer 22 having a thickness of 12 μm in Test Example 1. In this case, the three resin layers having the same composition were formed from recycled PET regenerated by mechanical recycling and virgin PET.

[0074] In the PET layer 22 of Test Example 1, the mass of the recycled PET was set to 80% of the total mass of the resin film, and the mass of the virgin PET was set to 20% of the total mass of the resin film. In addition, the proportion of isophthalic acid in all dicarboxylic acid units in the recycled PET was specified based on the NMR measurement results, and the proportion of isophthalic acid in all dicarboxylic acid units in the PET layer 22 was set to 0.5 mol % or more and 5 mol % or less.

[0075] A first barrier layer made of aluminum oxide was laminated on the PET layer 22 of Test Example 1 by using a vacuum deposition method. The thickness of the first barrier layer was 10 nm. Furthermore, a second barrier layer was formed on the first barrier layer by using a direct gravure coating method, and a barrier layer 23 was laminated as a laminate of the first barrier layer and the second barrier layer. In this way, the laminate 20 of Test Example 1 was obtained.

[0076] In this case, hydrochloric acid was added to tetraethoxysilane, and the mixture was stirred for 30 minutes to hydrolyze the mixture, thereby preparing a hydrolysis solution. In addition, polyvinyl alcohol was dissolved in a mixed solvent of water and isopropyl alcohol to prepare a PVA solution. The hydrolysis solution and the PVA solution were mixed in a ratio of 60:40 to prepare a mixed solution for forming the second barrier layer. The mixed solution was applied onto the first barrier layer using a bar coater, and the formed coating film was dried in a dryer at 120°C for 1 minute to form the second barrier layer. The thickness of the second barrier layer was 300 nm.

[0077] [Test Example 2] Three PET films were laminated such that the second PET film was sandwiched between the two first PET films, forming a laminate having a thickness of 12 μm, thereby forming the PET layer 22 of Test Example 2. The laminate 20 of Test Example 2 was obtained in the same manner as in Test Example 1 except for the configuration of the PET layer 22.

[0078] The first PET film of Test Example 2 is made of recycled PET regenerated by chemical recycling. The second PET film of Test Example 2 is a film in which 80% by mass of recycled PET regenerated by mechanical recycling is mixed with 20% by mass of recycled PET regenerated by chemical recycling. The mass ratio of recycled PET contained in the PET layer 22 of Test Example 2 is 100% of the total mass of the PET layer 22.

[0079] [Test Example 3] Three PET films were laminated such that the second PET film was sandwiched between the two first PET films, forming a laminate having a thickness of 12 μm, thereby forming the PET layer 22 of Test Example 3. The laminate 20 of Test Example 2 was obtained in the same manner as in Test Example 1 except for the configuration of the PET layer 22.

[0080] The first PET film of Test Example 3 was made of virgin PET. The second PET film of Test Example 3 was made of recycled PET regenerated by chemical recycling. The mass ratio of recycled PET contained in the PET layer 22 of Test Example 3 was 70% of the total mass of the PET layer 22.

[0081] [Test Example 4] A single layer PET film made of virgin PET was used as the PET layer 22. The PET layer 22 of Test Example 4 is a PET layer that does not contain recycled PET, and is made of polyethylene terephthalate in which the dicarboxylic acid unit in the repeating unit is only terephthalic acid. The thickness of the PET layer 22 of Test Example 4 is 12 μm. The laminate 20 of Test Example 4 was obtained in the same manner as in Test Example 1 except for the configuration of the PET layer 22.

[0082] [Evaluation method] [Evaluation 1: Yield stress] Three test pieces were cut out from each of the PET layers 22 in Test Examples 1 to 4. At this time, a dumbbell cutter (SDK-600, Dumbbell Co., Ltd.) conforming to JIS Z 1702-1994 was used to cut out each test piece so as to have a shape extending along the flow direction. That is, the test pieces were cut out from the PET layer 22 so that the tensile direction of each test piece coincided with the flow direction of the PET layer 22. Two benchmark lines for measuring elongation were then marked on each test piece.

[0083] Using a small tabletop testing machine (EZ-LX, manufactured by Shimadzu Corporation), the test pieces were Tensile tests were conducted using a method in accordance with K7161-1:2014. Each test piece was fixed to a small benchtop testing machine, and the gauge was clamped with an extensometer. The test speed was set to 300 mm / min. For each test example, a stress-strain curve was created based on the results of the tensile test on one test piece. From the stress-strain curve, the yield stress, the breaking strength, and the slope after yielding and in the range of strain 0.2 to 0.4 were obtained.

[0084] [Evaluation 2: Dynamic elastic modulus] A strip-shaped test piece was prepared from each of the PET layers 22 of Test Examples 1 to 4. The length of the test piece was 20 mm, and the width of the test piece was 10 mm. The flow direction (MD direction) during the formation of the PET layer 22 was set as the length direction of the test piece. The storage modulus G1 and loss modulus G2 of each test piece were measured using a thermomechanical analyzer (Hitachi High-Tech Science: DMA7100), and the loss tangent tanδ was calculated. The measurement conditions were as follows. Frequency: 10Hz Tension condition: Strain amplitude 10μm : Minimum tension / compression force 50mN :Tension / Compression Gain 1.2 : Initial force amplitude 50mN Heating conditions: Heating rate 2℃ / min :Heating temperature 30℃~180℃

[0085] [Rating 3: Barrier function] Two test pieces were prepared from each of the laminates 20 of Test Examples 1 to 4, and the gas barrier function was evaluated before and after the Gelbo flex test. The Gelbo flex test, the oxygen permeability measurement, and the water vapor permeability measurement were performed under the conditions described below.

[0086] [Gelboflex test] A Gelbo Flex test was performed on each test piece using a flexibility evaluation device (Gelbo Flex Tester, manufactured by Tester Sangyo Co., Ltd.). At this time, each test piece was attached to the fixed head of the flexibility evaluation device so as to have a cylindrical shape. In detail, both ends of each test piece were held by the fixed head, and the initial gripping distance was set to 175 mm. Then, the stroke was set to 87.5 mm, the twist was set to 440°, and each test piece was twisted and released from the twist, and the reciprocating motion was performed 10 times at a speed of 40 times / min.

[0087] [Oxygen permeability] The oxygen permeability of each test piece was measured before and after the Gelbo Flex test using an oxygen permeability measuring device (OX-TRAN 2 / 20, manufactured by Mocon). The method used was in accordance with JIS K 7126-2:2006 and ASTM D3985-81. The temperature was set to 30°C and the relative humidity was set to 70%. The unit of the measured oxygen permeability is [cm 3 (STP) / m 2 ·day·MPa].

[0088] [Water vapor permeability] The water vapor permeability of each test piece was measured before and after the Gelbo Flex test using a water vapor permeability measuring device (Mocon, PERMATRAN-W 3 / 31). The measurements were performed at a temperature of 40°C and a relative humidity of 90%. The measurement method used was in accordance with JIS K 7129-2:2019 and ASTM F1249-90. The unit of the measured water vapor permeability is [g(STP) / m 2 -day] was set.

[0089] [Evaluation result 1: Yield stress] The yield stresses in the machine direction of Test Examples 1 to 3 were 116.0 MPa, 115.0 MPa, and 110.2 MPa, respectively, and were found to be within the range of 109 MPa or more and 117 MPa or less as shown in Condition 1. In contrast, the yield stress of Test Example 4 was found to be 124.8 MPa.

[0090] The post-yield slopes of Test Examples 1 to 3 were 77.3, 110.5, and 84.2, respectively, and were found to be within the range of 75 to 111 specified in Condition 2. In contrast, the average value of the post-yield slopes of Test Example 4 was found to be 172.4.

[0091] The breaking strengths in the machine direction of Test Examples 1 to 3 were 170.9, 176.4, and 159.6, respectively, and were found to be within the range of 153 MPa or more and 183 MPa or less as shown in Condition 3. In contrast, the average value of the gradient after yield in Test Example 4 was found to be 202.7 MPa.

[0092] [Evaluation result 2: Dynamic modulus of elasticity] The measurement results of the storage modulus G1, loss modulus G2, and loss tangent tan δ of Test Examples 1 to 3 are shown in Table 1.

[0093] [Table 1] The measured value of the storage modulus G1 was obtained from the transition temperature T1 of the storage elastic curve shown in Figure 4 and the storage modulus G1 at the transition temperature T1. The measured value of the loss modulus G2 was obtained from the temperature T2 at the peak position of the loss elastic curve shown in Figure 5 and the loss modulus G2 at the temperature T2. The measured value of the loss tangent tanδ was obtained from the temperature T3 at the peak position of the loss tangent curve shown in Figure 6 and the loss tangent tanδ at the temperature T3.

[0094] In this case, the temperature at the intersection of the approximation line on the lower temperature side of the inflection point of the storage elasticity curve and the approximation line on the higher temperature side of the inflection point was defined as the transition temperature T1. The approximation line on the lower temperature side and the approximation line on the higher temperature side were obtained by approximating the set of measurement points on the lower temperature side and the set of measurement points on the higher temperature side, respectively. The set of measurement points on the lower temperature side is the inflection point and a plurality of measurement points between a point about 10°C lower than the inflection point and a point about 5°C lower than the inflection point. The set of measurement points on the higher temperature side is the inflection point and a plurality of measurement points between a point about 5°C higher than the inflection point and a point about 10°C higher than the inflection point.

[0095] The transition temperatures T1 of Test Examples 1 to 3 were 87.6°C, 87.8°C, and 80.3°C, respectively, and were all found to be within the range of 80°C or higher and 88°C or lower, as shown in Condition 4. The transition temperature T1 of Test Example 4 was found to be 87.0°C.

[0096] The storage modulus G1 of Test Examples 1 to 3 was 3.8 GPa, 4.1 GPa, and 3.9 GPa, respectively, and it was confirmed that all of them were within the range of 3.8 GPa or more and 4.1 GPa or less as shown in Condition 4. In contrast, the storage modulus G1 of Test Example 4 was confirmed to be 4.7 GPa. 3 It was found that the elasticity of the PET layer 22 in this test example was weaker than that of the PET layer 22 in the test example 4. 3 It was also found that the elasticity of the PET layer 22 weakens as the mass proportion of recycled PET increases.

[0097] The temperatures T2 at the peak positions in the loss elasticity curves of Test Examples 1 to 3 were 101.3°C, 99.8°C, and 95.4°C, respectively, and were all found to be within the range of 95°C to 102°C as specified in Condition 5. In contrast, the temperature T2 at the peak position in the loss elasticity curve of Test Example 4 was found to be 104.7°C. In other words, it was found that the flexibility at low temperatures of the PET layer 22 of Test Examples 1 to 3 was higher than that of the PET layer 22 of Test Example 4. In addition, 3 It was also found that the flexibility of the PET layer 22 at low temperatures increased as the mass proportion of recycled PET increased.

[0098] The loss modulus G2 of Test Examples 1 to 3 was 0.34 GPa, 0.37 GPa, and 0.37 GPa, respectively, and all of them were found to be within the range of 0.3 GPa or more and 0.37 GPa or less as specified in Condition 5. In contrast, the loss modulus G2 of Test Example 4 was found to be 0.39 GPa.

[0099] The temperatures T3 at the peak positions in the loss tangent curves of Test Examples 1 to 3 were 114.8°C, 113.8°C, and 108.8°C, respectively, and were found to be 108°C or higher and 115°C or lower in all cases. In contrast, the temperature T3 at the peak position in the loss tangent curve of Test Example 4 was found to be 119.0°C.

[0100] The loss tangent tanδ at the peak position in the loss tangent curve of Test Example 1 to Test Example 3 was 0.162, 0.170, and 0.185, respectively, and it was recognized that all of them were 0.160 or more and 0.190 or less as specified in Condition 6. In contrast, the loss tangent tanδ at the peak position in the loss tangent curve of Test Example 4 was 0.157. 3 It was found that in the PET layer 22, the degree of viscosity relative to elasticity was greater than in Test Example 4, and the contribution of viscosity in the response to an external force was also greater than in Test Example 4.

[0101] [Evaluation result 3: Barrier function] The measurement results of the oxygen permeability and the water vapor permeability of the laminate 20 of Test Examples 1 and 4 are shown in Table 3. 3 It was found that the oxygen permeability and water vapor permeability of the laminate 20 showed the same tendency as in Test Example 1, compared to Test Example 4.

[0102] [Table 2] As shown in Table 2, the oxygen permeability of the laminate 20 of Test Example 1 was 0.7 (cm 3 / m 2 ·day·MPa), while after the Gelbo Flex test it was 93.1 (cm 3 / m 2 It was found that the tensile strength increased to 1.5 MPa.

[0103] In contrast, the oxygen permeability of the laminate 20 of Test Example 4 was 0.6 (cm 3 / m 2 ·day·MPa), and after the Gelbo Flex test, it was 152.7(cm 3 / m 2 It was found that the tensile strength increased to 1.5 MPa.

[0104] As a result, it was found that the decrease in oxygen permeability in the laminate 20 of Test Example 1 was sufficiently smaller than that in the laminate 20 of Test Example 4, and that the laminate 20 of Test Example 1 was able to suppress the decrease in oxygen permeability more than the laminate 20 of Test Example 4.

[0105] The water vapor permeability of the laminate 20 of Test Example 1 was 0.07 (g / m 2 ·day), while after the Gelboflex test it was 0.97 (g / m 2 It was found that the serotonin concentration increased to 1.5 ng / day.

[0106] In contrast, the water vapor permeability of the laminate 20 of Test Example 4 was 0.19 (g / m 2 ·day), and after the Gelbo Flex test, it was 1.80 (g / m 2 It was found that the serotonin concentration increased to 1.5 ng / day.

[0107] As a result, it was found that the decrease in water vapor permeability in the laminate 20 of Test Example 1 was significantly smaller than that in the laminate 20 of Test Example 4, and that the laminate 20 of Test Example 1 was able to suppress the decrease in water vapor permeability more than the laminate 20 of Test Example 4.

[0108] In other words, it was found that if the parameters of the yield stress, the slope of the strain curve after yield, the breaking strength, the storage modulus G1, the loss modulus G2, and the loss tangent tanδ satisfy the above conditions 1 to 6, respectively, the flexibility of the laminate 20 can be suitably obtained, and as a result, the deterioration of the barrier property in the outer bag for a small-volume liquid agent can be suppressed.

[0109] As described above, according to the above embodiment, the following effects can be obtained. (1) Since the dicarboxylic acid units in the repeating units contain polyethylene terephthalate, which contains terephthalic acid and isophthalic acid, the deterioration of the barrier function of the outer bag 10 for small-volume liquid agents due to deformation such as folding or twisting can be suppressed.

[0110] (2) When the barrier layer 23 is an inorganic oxide layer and the outer bag 10 for a small-volume liquid agent is transparent, it is possible to improve the visibility of the liquid agent bag through the outer bag 10 for a small-volume liquid agent. In addition, since the configuration does not employ a metal barrier layer having a high barrier function, it is more effective to suppress the deterioration of the barrier function of the PET layer 22.

[0111] (3) When a polypropylene layer is further provided as a protective layer and the barrier layer 23 is located between the polypropylene layer and the PET layer 22, the polypropylene layer protects the barrier layer 23, thereby enhancing the effectiveness of suppressing the deterioration of the barrier function. In addition, when the polypropylene layer is located as the outermost layer, the frequency of occurrence of pinholes in the outer bag 10 for small-volume liquid agent can be suppressed.

[0112] (4) When a printed layer is further provided between the polypropylene layer and the barrier layer 23, the polypropylene layer protects the printed layer, making it possible to suppress a decrease in durability of the printed layer caused by deformation such as folding or twisting. In addition, the barrier layer located between the printed layer and the liquid agent bag also has a barrier function against the components of the printed layer. [Explanation of symbols]

[0113] 10...External bag for small volume liquid medicine 11...Sealing part 20...Laminate 21…Sealant layer 22...Polyethylene terephthalate layer 23...Barrier layer

Claims

1. An outer bag for a small volume liquid agent for packaging a small volume liquid agent bag, A barrier layer; A sealant layer having thermoplastic properties; a polyethylene terephthalate layer located between the barrier layer and the sealant layer, the polyethylene terephthalate layer contains polyethylene terephthalate containing terephthalic acid and isophthalic acid in dicarboxylic acid units in a repeating unit, The proportion of isophthalic acid in the total dicarboxylic acid units of the polyethylene terephthalate layer is 0.5 mol % or more and 5 mol % or less. Outer bag for small volume liquid medication.

2. the barrier layer is an inorganic oxide layer, The outer packaging bag for small-volume liquid preparation is transparent. The outer bag for a small volume liquid agent according to claim 1.

3. Further comprising a polypropylene layer; The barrier layer is located between the polypropylene layer and the polyethylene terephthalate layer. The outer bag for a small volume liquid preparation according to claim 1 or 2.

4. Further comprising a printing layer, The printing layer is located between the polypropylene layer and the barrier layer. The outer bag for a small volume liquid agent according to claim 3.

5. The polyethylene terephthalate layer is a laminate containing terephthalic acid and isophthalic acid in the dicarboxylic acid unit in the repeating unit of the polyethylene terephthalate contained in each layer. The outer pouch for a small-volume liquid agent according to any one of claims 1 to 4.

6. The small volume is 100 ml or less. The outer pouch for a small volume liquid agent according to any one of claims 1 to 5.

7. A method for manufacturing an outer bag for packaging a small-capacity liquid agent bag, comprising: laminating a barrier layer to the polyethylene terephthalate layer; and laminating a sealant layer having thermoplasticity on the polyethylene terephthalate layer such that the barrier layer and the sealant layer sandwich the polyethylene terephthalate layer; the polyethylene terephthalate layer contains polyethylene terephthalate containing terephthalic acid and isophthalic acid in dicarboxylic acid units in a repeating unit, The proportion of isophthalic acid in the total dicarboxylic acid units of the polyethylene terephthalate layer is 0.5 mol % or more and 5 mol % or less. A method for manufacturing an outer bag for small-volume liquid drugs.

Citation Information

Patent Citations

  • Exterior bag for transfusion container

    JP2001048246A

  • Transparent packaging bag and liquid pharmaceutical product package externally packaged with transparent packaging bag

    JP2004051174A

  • Outer packaging bag for infusion solution bag

    JP2007075368A

  • Exterior bag for transfusion

    JP2011140327A

  • Eyedrop container package

    WO2015060377A1